A novel approach to fixture design based on locating correctness. (6th October 2010) - Qin, G.H.; Zhang, W.H.; Wan, M.; Sun, S.P.
In a machining process, since the geometric accuracy of a manufacturing workpiece mainly relies on the relative position of workpiece to the machining tool, fixtures are needed to locate the workpiece. The clear concept of locating correctness is presented based on Venn diagram and a general algorithm is proposed to determine the locator number and layout. On one hand, the theoretical and practical constrained DOFs are formulated as a function of the machining requirement and the locating scheme, respectively. On the other hand, some criteria are concluded to analyse the locating correctness and modify the locating scheme with locating incorrectness.